2020
DOI: 10.3390/microorganisms8020166
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial, Gut Microbiome-Modifying Therapies to Defend against Multidrug Resistant Organisms

Abstract: Antibiotics have revolutionized human and animal healthcare, but their utility is reduced as bacteria evolve resistance mechanisms over time. Thankfully, there are novel antibiotics in the pipeline to overcome resistance, which are mentioned elsewhere in this special issue, but eventually bacteria are expected to evolve resistance to most new compounds as well. Multidrug resistant organisms (MDROs) that cause infections increase morbidity, mortality, and readmissions as compared with susceptible organisms. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Only a few studies have addressed this question since 2020. In line with earlier reviews on the same topic [ 16 , 17 , 34 , 35 ], decolonisation rates varied greatly. Although only two studies reported decolonisation rates for CRE and VRE separately and sample sizes were small, decolonisation rates were higher for CRE patients, with a large effect size compared to controls.…”
Section: Discussionsupporting
confidence: 73%
“…Only a few studies have addressed this question since 2020. In line with earlier reviews on the same topic [ 16 , 17 , 34 , 35 ], decolonisation rates varied greatly. Although only two studies reported decolonisation rates for CRE and VRE separately and sample sizes were small, decolonisation rates were higher for CRE patients, with a large effect size compared to controls.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, these drugs also cause profound gastrointestinal dysbiosis of the protective microbiota, leaving treated individuals with often dangerous secondary outcomes [47]. Selective decolonization of pathogenic bacteria as a way to minimize their translocation and horizontal transmission to other patients is currently being explored in the pharmaceutical industry by assembling consortia of isolated bacteria that display decolonizing properties against certain species, including K. pneumoniae [48]. However, to our knowledge there is no biotherapeutic yet that has reach stage for human trials.…”
Section: (N=8) Discussionmentioning
confidence: 99%
“…The resulting unassembled sequencing reads underwent multi-kingdom microbiome analysis and profiling of antibiotic resistance genes using the CosmosID bioinformatics platform (CosmosID Inc., Rockville, MD), as described elsewhere 107,108 . The antibiotic resistance and virulence genes in the microbiome were identified by querying the unassembled sequence reads against the CosmosID-curated antibiotic resistance and virulence associated gene databases 109,110 .…”
Section: Methodsmentioning
confidence: 99%